Essence of information human rights in science of information law - Калюжний, К. Р. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article the essence of information rights in modern society, with emphasis on basic informationrights and freedoms of man and citizen, and outlines the level of their implementation.